2018
DOI: 10.1037/xhp0000554
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity indicates processing level of visual illusions.

Abstract: A nearly linear contrast response function (CRF) is found in the lower level striate cortex whereas a steep, nonlinear increase at lower contrasts that gradually increases toward response saturation for higher contrasts is found in the higher level extrastriate cortex. This change of CRFs along the ventral cortical pathway indicates a shift from stimulus- and energy-dependent coding at lower levels to percept- and information-dependent coding at higher levels. The increase of nonlinearity at higher levels opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Another implication is that the proposed approach supports applying our rationale to studying the comparative processing levels of many additional visual phenomena such as visual illusions. We [93] are currently applying it to investigations of the processing levels of simultaneous brightness induction, a version of the tilt illusion different from the one used by Pearson and Clifford, the Ponzo illusion, as well as the White effect [94]. Using our version of the simultaneous tilt illusion, we replicated Pearson and Clifford’s tilt-illusion results obtained when the inducer was visible (see Figure 3).…”
Section: Discussion Implications and Directions For Further Resesupporting
confidence: 59%
“…Another implication is that the proposed approach supports applying our rationale to studying the comparative processing levels of many additional visual phenomena such as visual illusions. We [93] are currently applying it to investigations of the processing levels of simultaneous brightness induction, a version of the tilt illusion different from the one used by Pearson and Clifford, the Ponzo illusion, as well as the White effect [94]. Using our version of the simultaneous tilt illusion, we replicated Pearson and Clifford’s tilt-illusion results obtained when the inducer was visible (see Figure 3).…”
Section: Discussion Implications and Directions For Further Resesupporting
confidence: 59%
“…Peak differences between striate and extra-striate CRFs were found around the time where striate cortex responses start to saturate (for more comprehensive figures, see also Brown et al, 2018). In this context, one can interpret the saturation of extra-striate activity in the CRF as the peak of information-driven/percept-driven processing (as opposed to energy-driven/stimulus-driven processing; e.g., 67 , 70 ). Here we propose to extrapolate over the methodological differences between our study and Hall et al 85 , and to interpret this result as indicating that (1) peak Gestaltness is observed when the visual system switches from stimulus- and energy-dependent processing to percept- and information-dependent processing and that (2) Gestalts differentially engage higher-order visual processing areas, even when dealing with “pure Gestalt” (i.e., the two-dot pure emergent feature stimuli).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the well-established notion that, along the hierarchy of cortical visual processing, responses change from being dependent on stimulus energy (e.g., contrast, size) at low levels to being percept and information-dependent at higher-order areas (for other examples, see 67 69 . In the field of pure psychophysics, Brown et al 70 found that the changes in illusion magnitude as a function of stimulus contrast were linear for illusions that relied more strongly on low processing levels (e.g., simultaneous brightness and simultaneous tilt) and nonlinear for illusions that rely more strongly on contextual information and higher processing levels (e.g., the Ponzo and Poggendorff illusions).…”
Section: Introductionmentioning
confidence: 99%
“…But there is recent evidence that even simpler versions depend on higherlevel information. Brown, Breitmeyer, Hale, and Plummer (2018) measured the contrast response function (CRF) for the traditional simple Ponzo illusion, i.e., how the magnitude of the illusion changes as a function of the contrast of inducing stimuli (i.e., the converging lines). They found non-linear changes in the CRF for the Ponzo illusion, indicating a dependence on higher-level perceptual coding (e.g., perceived size and distance).…”
Section: Discussionmentioning
confidence: 99%